2008
DOI: 10.1016/j.juro.2008.08.078
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Dietary Supplement Intervention Trials for the Prevention of Prostate Cancer Recurrence: A Review of the Randomized Controlled Trial Evidence

Abstract: A limited number of randomized controlled trials were identified in which diet and dietary supplement interventions appeared to slow disease progression in men with prostate cancer, although results vary. Studies were limited by reliance on the surrogate biomarker prostate specific antigen, sample size and study duration. Well designed trials are warranted to expand knowledge, replicate findings and further assess the impact of diet and dietary supplement interventions on recurrence and treatment associated mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 43 publications
1
32
0
1
Order By: Relevance
“…Diet has also been linked to prostate cancer progression and recurrence and clinical studies indicate that adopting a plant--based diet can reduce the rate of increase in prostate specific antigen (PSA) in men diagnosed with low--grade prostate cancer (Arab et al, 2013;Nguyen et al, 2006;Ornish et al, 2005;Van Patten, de Boer, & Tomlinson Guns, 2008). Because PSA can be used as a proxy marker of prostate cancer progression, these findings suggest that diet changes can potentially slow or stop prostate cancer growth and thus delay the need for treatments and decrease the substantial burden of treatment side--effects men with prostate cancer face (Berkow, Barnard, Saxe, & Ankerberg--Nobis, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Diet has also been linked to prostate cancer progression and recurrence and clinical studies indicate that adopting a plant--based diet can reduce the rate of increase in prostate specific antigen (PSA) in men diagnosed with low--grade prostate cancer (Arab et al, 2013;Nguyen et al, 2006;Ornish et al, 2005;Van Patten, de Boer, & Tomlinson Guns, 2008). Because PSA can be used as a proxy marker of prostate cancer progression, these findings suggest that diet changes can potentially slow or stop prostate cancer growth and thus delay the need for treatments and decrease the substantial burden of treatment side--effects men with prostate cancer face (Berkow, Barnard, Saxe, & Ankerberg--Nobis, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review included a mixed supplementation study and focused on RCTs only. 25 We incorporated information from studies examining only lycopene supplementation to identify more clearly its effect on prostate cancer. Moreover, we included all types of intervention studies rather than only RCTs.…”
Section: Strengths/limitations Of the Reviewmentioning
confidence: 99%
“…We also did not include the term 'trials' or relevant synonyms in the search strategy in case some of the reports with these designs were not appropriately classified. Moreover, unlike the review by Van Petter et al, 25 we did not restrict the language of publication to English and we did not restrict the year of publication.…”
Section: Strengths/limitations Of the Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Around the globe federal and government efforts have accumulated on consensus for statutory policy to use nutraceuticals on their daily requirements, supplementation, combinations and dosage to prevent or manage the cancer [79][80][81][82][83]. Randomized and double blind control trials indicated the increased importance of vitamins, herbs and fresh vegetables as likely protective supplements [84][85][86][87][88][89][90], tomato (lycopene) in prostate cancer prevention [91][92][93], nutritional intervention in different cancers of different body organs in the body [94][95][96][97][98][99][100]. New concept of Mediterranean diet was introduced to reduce the risk of cancer along with cardioprotection [101][102][103][104].…”
Section: Nutraceuticals In Cancer Prevention During Years 2002-2008mentioning
confidence: 99%